Karl Schmückle is unknown companion on the Tuvan journey of Otto Menchen-Helfen - Shafranskaya, Eleonora F.; Dolzhikova, Angela V. (The New Research of Tuva, 2024)
The article introduces Karl Karlovich Schmückle, who was a companion of Otto Menchen-Helfen during their trip to Tuva in 1929. Although there is a rich literature about Menchen-Helfen, beginning with his book “Reise ins Asiatische Tuwa” (1931), Schmückle became a persona non grata figure in the history of the 20th century. The reason for this is that he was arrested in 1937 and executed in 1938. Many researchers have attributed the authorship of an article about the trip to Tuva to Menchen-Helfen prior to his book. However, the origin of this article is often confused, as the identity of its author and the title are missing from scientific discourse or given with distortion. This article provides full information about the article, its full text, and its author, Karl K. Schmückle. A short biographical sketch of Schmuckler is also given in the article.